Answer: -7
=========================================================
Reason:
The equation −8x−10y=3 is the same as 8x+10y = -3 after multiplying both sides by -1
We have this system of equations
![\begin{cases}-6x+y = -4\\8x+10y = -3\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1txpvc2gs5okbgjf5sr89splt9cp7q04fp.png)
Add the equations straight down.
- -6x+8x becomes 2x
- y+10y becomes 11y
- the right hand sides combine to -4+(-3) = -7
Therefore, we end up with the equation 2x+11y = -7
An alternative is to solve the system using substitution to get the (x,y) intersection point. Then use those coordinates to compute 2x+11y and you should get -7 as a result.